Minnie Maddern Fiske and Harrison Grey Fiske papers - Fiske, Minnie Maddern, 1865-1932.; Fiske, Harrison Grey, 1861-1942.
Correspondence, play scripts, prompt books, playbills, box office receipts and invoices, financial and legal records, scrapbooks, newspaper clippings, photographs, broadsides, illustrations, drawings, certificates, set design drawings and blue prints, and drafts of plays, speeches, and articles written by Minnie Maddern Fiske and her husband, Harrison Grey Fiske, documenting her theatrical career and life and his work as theater critic and manager, playwright, director, and producer of plays for the American stage. Includes material relating to the continuing controversy between the Fiskes and the theatrical trusts of the period, the 1919 strike by the Actor's Equity Association, animal welfare, and the anti-vivisectionist movement. Correspondents include Gertrude Franklin Horn Atherton, J.M. Barrie, David Belasco, Daniel Chester French, Jack London, John Philip Sousa, Alexander Woollcott, and Flo Ziegfeld.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Music Division.
Library of Congress Prints and Photographs Division.
Minnie Maddern Fiske, actress; and her husband, Harrison Grey Fiske, theater manager.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Atherton, Gertrude Franklin Horn, -- 1857-1948 -- Correspondence; Barrie, J. M. -- 1860-1937 -- Correspondence; Belasco, David, -- 1853-1931 -- Correspondence; French, Daniel Chester, -- 1850-1931 -- Correspondence; London, Jack, -- 1876-1916 -- Correspondence; Sousa, John Philip, -- 1854-1932 -- Correspondence; Woollcott, Alexander, -- 1887-1943 -- Correspondence; Ziegfeld, Flo, -- 1869-1932 -- Correspondence; Actors' Equity Association; Acting; Animal welfare; Dramatic criticism; Labor unions -- United States; Theater -- Finance; Theater -- Production and direction; Theater -- United States; Theater management; Strikes and lockouts; Vivisection; Actresses; Theater managers